REALITAS DAN STRATEGI MENGENTASKAN KEMISKINAN di SEKTOR TANAMAN PANGAN (Studi Kasus: Jawa Barat dan Sulawesi Selatan) - Darwis, Valeriana; Muslim, Chairul (Indonesian Journal of Socio Economics)
Poverty is always there in every state and many businesses to Improved the life of him. Poverty is everywhere, and most are in Village. While the majority of the village population works in agriculture. This paper is part of the research reports Patanas 2007 that shows the reality and strategies used anticipation farmers crops. Source of income and expenditure for food needs, is one indicator of poverty. Fall-time income and most of the respondents came from agriculture, whether it comes from their own land or become farmer labor in the land people. Consumption average half of the total income used to meet their food needs with the source of carbohydrate comes from rice, protein from the source and know where meat consumption is felt only on certain days only. Strategies to overcome the food needs in a way to plant rice in field with the commodity, so it can be consumed or sold when the price attractive. In conditions that concern the needs of food owing to the way by others or eating rice aking. Strategies to the needs of clothing is generally obtained at the time of wordiness and buy clothing with the quality and the cheap price. Health needs, in principle, does not provide special funds, if the pain is quite traditional medicine, herbal medicine or increase the rest time. Education needs in the tactics with a search for a location not far from home, the needs of school uniforms or equipment with a cheaper way to buy or take the school uniform or equipment from sister or neighbor who is still eligible to use. To overcome the problem of poverty is the government implementing the policy in the upstream in the form of maintaining the free give away seed, fertilizer and subsidy make special financial institutions and agricultural policy in the downstream in the form of maintaining the price of unhulled rice and implement agricultural insurance.